Answer:
C is the only one equivalent
Explanation:
A. 5x − 3y = 6
6x − 2y = 8
Resolving the orginial system and this system we have
5x − 3y = 6 → 5x − 3y = 6 → -8y = - 4 → y=2 → x=0
(-5)(x + y = 2) -5x -5y = -10
A. 5x − 3y = 6 → 5x − 3y = 6 → -4x = -6 → x=3 → y=3
( -3/2)(6x − 2y = 8) - 9x + 3y = -12
A is not an equivalent system because the 2nd eq of each one have a different solution
B. 5x − 3y = 6
2x + 2y = 2
Resolving the orginial system and this system we have
5x − 3y = 6 → 5x − 3y = 6 → -8y = - 4 → y=2 → x=0
(-5)(x + y = 2) -5x -5y = -10
B 5x − 3y = 6 → 5x − 3y = 6 → 8x = 9 → x=9/8→ y= -1/8
(3/2)(2x + 2y = 2) 3x + 3y = 3
B is not an equivalent system because the 2nd eq of each one have a different solution
C. −5x − 3y = 6
x + y = 2
C is the same system of the original
D. 5x − 3y = 6
6x − 2y = 2
Resolving the orginial system and this system we have
5x − 3y = 6 → 5x − 3y = 6 → -8y = - 4 → y=2 → x=0
(-5)(x + y = 2) -5x -5y = -10
D 5x − 3y = 6 → 5x − 3y = 6 → 2x = 2 → x=1→ y= - 1/3
(-3/2)(6x − 2y = 2) - 3x + 3y = -3
D is not an equivalent system because the 2nd eq of each one have a different solution